Conceptual and theoretical analysis of the concept of ethnos: from objective reality to the imaginary construction - Kurbacheva, Olga V. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The main purpose of this article is to conceptual and theoretical analysis of the concept of ethnos. In this article provides a historical and philosophical insight into the emergence of terminology. The author reveals the differences of such concepts as «ethnicity», «race», «tribe», «ethnicity», «people», «nation». The article also analyzes the significance of the process of ethnogenesis. The author draws attention to different approaches to understanding the nature of ethnicity: primordialism, constructivism, instrumentalism. The article notes that today in the understanding of the essence of the ethnic group the transition from anthropogenetic markers to symbolic characteristics is carried out.